2005
DOI: 10.1007/s00122-005-0169-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci analysis for the developmental behavior of Soybean (Glycine max L. Merr.)

Abstract: Quantitative trait loci (QTLs) identified so far in soybean were mainly derived in the final stage of plant development, which did not apply to the exploitation of genetic effects that were expressed during a specific developmental stage. Thus, the aim of this study was to identify conditional QTLs associated with yield traits at a specific developmental interval of soybean plant. The 143 recombinant inbred lines developed from the cross of soybean cultivars 'Charleston' and 'Dongnong 594' were used for the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
79
0
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 29 publications
9
79
0
8
Order By: Relevance
“…The association of developmental behavior of quantitative traits with molecular markers had been reported in rice and cotton (Wu et al, 1999;Ye et al, 2003;Yan et al, 1998a, b), and morphological traits and seed quality traits in soybean (Sun et al, 2006;Li et al, 2007;Xin et al, 2008). The main objective of the present study was to identify both conditional and unconditional QTL underlying the development of gain in seed weight and the QTL underlying final mean seed weight in soybean.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…The association of developmental behavior of quantitative traits with molecular markers had been reported in rice and cotton (Wu et al, 1999;Ye et al, 2003;Yan et al, 1998a, b), and morphological traits and seed quality traits in soybean (Sun et al, 2006;Li et al, 2007;Xin et al, 2008). The main objective of the present study was to identify both conditional and unconditional QTL underlying the development of gain in seed weight and the QTL underlying final mean seed weight in soybean.…”
Section: Introductionmentioning
confidence: 69%
“…Developmental programs are very important factors controlling the development of quantitative traits such as seed composition, yield and plant height (Yan et al, 1998b;Sun et al, 2006;Li et al, 2007). The development of some quantitative traits occurs through the actions and interactions of many genes.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, most QTL were detected at only one stage, and a few QTL were expressed in two continuous or separate stages. Sun et al (2006) and Zheng et al (2011) believe that this is the result of differential gene expression at different times. These results indicate that QTL/gene expression is timedependent during the entire developmental process.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, conditional QTL mapping, or a combination of unconditional and conditional QTL mapping has been used to study the dynamics of developmental traits. Sun et al [63] used conditional and unconditional mapping to study the developmental behavior of soybean. Yang et al [45] used conditional mapping to dissect the developmental behavior of tiller number and plant height, and found that conditional mapping was superior to conventional mapping for studying developmental traits.…”
Section: Dynamic Mapping For Developmental Traitsmentioning
confidence: 99%